Effect of Pre-Exposure of Human Erythrocytes to Oxidants on the Haemolytic Activity of Sticholysin Ii. a Comparison Between Peroxynitrite and Hypochlorous Acid - Lissi-Gervaso, E (Informa Healthcare, 2011)
Stichodactyla heliantus II (St II) is a haemolytic toxin whose activity depends of the characteristics of red blood cells (RBC). Among the factors that may tune the response of the RBC to the toxin activity stand the oxidative status of the cell. This study investigates how pre-oxidation of RBC modifies St II activity employing two oxidants, peroxynitrite and hypochlorous acid. Results show that peroxynitrite-treated RBC are more resistant to St II activity. On the other hand, hypochlorous acid-treated RBC become more susceptible to St II. This contrasting behaviour of both oxidants is related to the modifications elicited in RBC by both oxidant agents. Peroxynitrite does not modify RBC osmotic fragility but reduces anion transport through band 3 protein. This effect, together with an increase in K+ efflux, can explain the increased resistance to the toxin activity. On the other hand, results obtained with hypochlorous acid can be explained in terms of a disruption of the membrane organization without the compensating effect of a reduction in band 3-mediated anion transport. The present results, obtained employing the effect of a model haemolytic toxin on RBC, emphasize the specificity of the RBC response to different endogenous oxidative agents. © 2011 Informa UK, Ltd.